2020
DOI: 10.1515/med-2020-0124
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric symptoms, quality of life and caregivers’ burden in dementia

Abstract: The objective of this research is to identify the relationship between the neuropsychiatric symptoms (NPSs) of patients with major neurocognitive disorder (mNCD), their quality of life, illness intrusiveness and the caregiver’s burden. We assessed 131 patients with mNCD. Examination methods included WHO well-being index short version, illness intrusiveness rating scale, Alzheimer’s Disease Assessment Scale-Cog, Mini Mental State Examination and neuropsychiatric inventory. The results were analysed using standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
(33 reference statements)
3
7
0
Order By: Relevance
“…We found that NPS was associated with CB and there was a statistically significant relationship between all subcomponents of CB and NPS. The results of this study are in line with previous findings showing that the presence of NPS in people with AD is associated with both increased burden and lower quality of life in caregivers (37). Also, in the study by Chen et al, the results showed that NPI score was independently associated with mean NPI-burden score (38).…”
Section: Discussionsupporting
confidence: 91%
“…We found that NPS was associated with CB and there was a statistically significant relationship between all subcomponents of CB and NPS. The results of this study are in line with previous findings showing that the presence of NPS in people with AD is associated with both increased burden and lower quality of life in caregivers (37). Also, in the study by Chen et al, the results showed that NPI score was independently associated with mean NPI-burden score (38).…”
Section: Discussionsupporting
confidence: 91%
“…More importantly; our study is, to our knowledge, the first to investigate and find predictive links between premorbid maladaptive personality traits and the emotional distress of the caregiver associated with different BPSD. Our outcomes are highly relevant for clinical practice as little is known about BPSD, which are one of the main reasons of earlier institutionalization and create a great distress on the patient and their context 2 …”
Section: Discussionmentioning
confidence: 99%
“…Most patients with dementia suffer from at least one feature of BPSD 2 . BPSD can create a great distress on patient and caregiver 4 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 20%−30% of Americans and 8% of Chinese in the elderly population have health issues related to cognitive impairment [1]. Abnormal cognitive functioning impedes the quality of life and affects the disease burden for caregivers as well as patients [2]. It is more likely to further develop into worse impairments, such as Alzheimer's disease or dementia, and increase the risk of morbidity and mortality [3][4][5].…”
Section: Introductionmentioning
confidence: 99%